IMPROVING THE PERFORMANCE OF THE 476 CUTTING MACHINE AT PT RACHMAT PERDANA ADHIMETAL PLANT DELTA WITH OVERALL EQUIPMENT EFFECTIVENESS (OEE) - Janua'nsah, Danu Maulana; Rusmiati, Emi (Jurnal Teknologi dan Manajemen, 2025)
PT Rachmat Perdana Adhimetal is one of the manufacturing industries engaged in the manufacture of automotive and non-automotive components in the Delta industrial area, Cikarang, Bekasi Regency. In the implementation of the production process on the cutting line, the company experienced a breakdown problem. Of the 8 available cutting machines, there is 1 machine, the 476 cutting machine which has the highest breakdown frequency. To overcome these problems, data related to operating time, output and downtime is collected, followed by data processing using Overall Equipment Effectiveness (OEE) which can describe the efficiency of the machine. The results of data processing showed an OEE value of 68% of the standard value of 85%. Furthermore, an analysis was carried out with six big Losses, the results showed that there were 2 largest Losses, reduce speed Losses with a value of 14.90% and breakdown losses with a value of 12.65%. Followed by a cause analysis using a causal diagram to find out the factors that affect engine performance from machines and humans. To determine the priority of repairs made on the 476 cutting machine, an analysis was carried out using Failure Mode and Effect Analysis (FMEA). Priority for repairs based on the value of RPN 120 in the type of failure there is no wind pressure regulator with the repair of installing air speed adjuster/faucet, the value of RPN 102 in the type of failure of maintenance staff does not understand the daily checksheet with the improvement of the socialization of the daily checksheet to the maintenance staff, the value of RPN 54 in the type of failure 1/3 of the wind pressure is divided into the air sprayer and the value of RPN 21 in the type of failure leader does not understand the SOP for moving materials at the beginning of the set up with improvement of socialization of SOPs for moving materials at the beginning of the set up to the leader. The OEE value after the improvement showed a value of 77%, an increase of 9% from before the improvement.